Case report: Amplatzer septal occluder device migration into the descending thoracic aortic isthmus: percutaneous retrieval and redeployment - Xiang, Kun; Ai, Qi; He, Lin; Fan, Chengming (Frontiers in Cardiovascular Medicine, 2023)
Percutaneous closure has emerged as the standard treatment for secundum-type atrial septal defects (ASDs). However, there is a rare but serious complication of occluder device migration and embolization to the heart chambers or distal vasculature during or shortly after implantation. Although this occurrence is extremely rare, it can have disastrous consequences. Fortunately, advancements in equipment and technology have facilitated the transition from surgical procedures to percutaneous techniques for removing embolized occluder devices. In this report, we present a case in which an Amplatzer septal occluder (ASO) device embolized to the descending thoracic aortic isthmus two days after implantation. The device was successfully retrieved using a percutaneous technique, and another ASO device was subsequently redeployed to the ASD. Regrettably, the patient experienced an intraoperative cardiac arrest. Despite prompt rescue efforts and recovery of vital signs, the patient still suffered postoperative sequelae. The main reason for occluder device migration in this case may have been the undersizing of the ASO device due to the operator's lack of caution.